Influence of artificial cracks and interfacial defects on the corrosion behavior of steel in concrete during corrosion initiation under a chloride environment. (30th August 2020) - Zhang, Wulong; François, Raoul; Cai, Yuxin; Charron, Jean-Philippe; Yu, Linwen
Highlights: Air voids mainly appeared at the rib foot of reinforcement. Chlorides firstly penetrated from crack and migrated along top-casting defects. Initial points of corrosion are strongly related to the rib foot of reinforcement. Abstract: In this study, the effect of both artificial crack and defects of the steel-concrete interface on the initiation and propagation of steel reinforcement corrosion in concrete under a chloride environment is investigated. This work was based on two groups of reinforced concrete blocks, with or without artificial crack. The microstructures of the steel-concrete interface, the cement hydration products at the steel-concrete interface, the chloride profiles, the galvanic corrosion current, and the distribution of pitting corrosion on steel rebar were studied and compared. Experimental results show that the location of initial corrosion is related to top-casting defects but not to the location of air bubbles. Pitting corrosion mainly initiated at the rib foot of the bottom side of the deformed steel rebar with top-casting defects. Steel in concrete with an artificial crack exhibited a fast initiation period immediately followed by a propagation period. The presence of both artificial crack and top-bar effect thus led to faster deterioration than in un-cracked structures.